Raymie nightingale - DiCamillo, Kate (Candlewick Press, 2018)
After her father runs off with a dental hygienist, Raymie Clarke decides it is up to her to repair her family. She plans to win the Little Miss Central Florida Tire competition so her father will see her picture in the paper and come home. However, Raymie has competition in Beverly Tapinski and Louisiana Elefante. All of the girls want to win the pageant for different reasons, and none ever imagined they would become friends.